Pengaruh Model Pembelajaran Problem-Based Learning berbantuan Modul dan Jobsheet terhadap Hasil Belajar Instalasi Motor Listrik - Pertiwi, Devi; Darmawan, Ilham Akbar; Hamid, Mustofa Abi (Jurnal Pendidikan Teknik Elektro, 2024)
The purpose of this study was to determine the effect of the problem-based learning (PBL) learning model assisted by modules and jobsheets on learning outcomes in electric motor installation subjects. This research uses a quantitative approach, the research method used is the quasi-experiment method. The results of this study are: The learning outcomes obtained are not only in the form of increased knowledge but also improved thinking skills that can be applied to real problems. quasi-experimental research or quasi-experimental (quantitative). There is a significant effect of using the Problem-Based Learning model on learning outcomes in the experimental class, and there is an influence on learning outcomes in the control class. This shows that there is a significant difference between the average post-test scores of the experimental class and the post-test scores of the control class using the Problem-Based Learning model assisted by Modules and Jobsheets in learning outcomes in the Electric Motor Installation subject. Then there is the influence of the Problem-Based Learning model on student learning outcomes in the eyes of Electric Motor Installation.